ANALISIS RISIKO K3 PADA MAINTENANCE MESIN FINAL PRESS MENGGUNAKAN METODE SWIFT - Ma'ruf, Anang; Lasalewo, Trifandi; Giu, Jamal Darussalam (Universitas Bina Taruna Gorontalo, 2023)
This study aims to determine the hazards that arise as a result of the final press machine maintenance process and to provide a solution to the existing hazards in the form of safeguards or recommendations for improvement. The method used in this study is the SWIFT (Structural What If Analysis) method, which is a technique for identifying the dangers of a questioning approach using the what if keyword. System design is carried out to evaluate the company's occupational safety and health system by examining the causes and implementing corrective solutions. In this paper, the results of this study were carried out using a qualitative method by conducting an analysis on maintenance activities for the final press machine which resulted in risks with different levels, namely 13 medium priorities, 3 low priorities and 4 lowest priorities with the conclusion that the medium priority would be recommended for system improvement because it has the highest priority value which aims to prevent and reduce the risk level of work accidents in the final press machine maintenance process. Suggestions for companies to pay more attention to the safety and health of workers in order to achieve a comfortable and safe work system for workers by providing PPE, and there needs to be an emphasis on implementing efforts to control work accidents for workers to minimize the risk of work accidents.